Метрологическое обеспечение машиностроительных производств - Kuzmichev K. D. (Students' science: current realities, 2017)
This article lists the main tasks that must be performed by the metrological support of production, and demonstrates the necessity of using the capabilities of modern software complexes that allows to carry out situational modeling of degradation and destruction.
Keywords: информационные технологии; параметры; технологический процесс; контроль качества; Information technology; метрология; quality control; metrology; parameters; process technology